2016
DOI: 10.1186/s12977-015-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 latency and virus production from unintegrated genomes following direct infection of resting CD4 T cells

Abstract: BackgroundHIV-1 integration is prone to a high rate of failure, resulting in the accumulation of unintegrated viral genomes (uDNA) in vivo and in vitro. uDNA can be transcriptionally active, and circularized uDNA genomes are biochemically stable in non-proliferating cells. Resting, non-proliferating CD4 T cells are prime targets of HIV-1 infection and latently infected resting CD4 T cells are the major barrier to HIV cure. Our prior studies demonstrated that uDNA generates infectious virions when T cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(142 citation statements)
references
References 99 publications
(152 reference statements)
9
132
1
Order By: Relevance
“…Integrase inhibitors effectively suppress the integration of these new HIV DNA forms, but cannot prevent the production of viral proteins derived from the episomal HIV DNA forms which accumulate due to the blockage of viral integration. Our data are supported by recent reports that also suggest a contribution of unintegrated DNA to viral gene expression in resting CD4+ T cells1923.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Integrase inhibitors effectively suppress the integration of these new HIV DNA forms, but cannot prevent the production of viral proteins derived from the episomal HIV DNA forms which accumulate due to the blockage of viral integration. Our data are supported by recent reports that also suggest a contribution of unintegrated DNA to viral gene expression in resting CD4+ T cells1923.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that episomal HIV DNA can lead to the production of HIV proteins and may even generate fully replication competent viruses202122. However, the implications of transcription from 2-LTR circles, especially in the context of HIV latency, have remained underestimated and incompletely understood1923.…”
mentioning
confidence: 99%
“…ϩ T cells (58)(59)(60)(61). To exclude the possibility that some forms of this unintegrated HIV-1 DNA become integrated upon T cell activation, resulting in productive infection and virus particle production, we next assessed the contribution of unintegrated HIV-1 LAI DNA to extracellular vRNA production from both T N and T CM cells by including the integrase inhibitor raltegravir (RAL) at the same time as anti-CD3/CD28 (Fig.…”
Section: Resting Cd4mentioning
confidence: 99%
“…Thus monocytes cannot serve as a long-lived reservoir. Tissue-resident macrophages derived from monocytes have a relatively short half-life on the order of weeks, depending on the tissue (Ginhoux & Guilliams 2016), while those derived from embryonic hematopoetic precursors have a longer half-life of 24–36 months (Kandathil et al 2016). Integrated proviral DNA has been observed in brain astrocytes and microglia (Churchill et al 2006), which have half-lives on the order of months and years, respectively (Marban et al 2016).…”
Section: Other Clinically Relevant Reservoirs In the Quest For A Curementioning
confidence: 99%